2003
DOI: 10.1194/jlr.m300272-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan for quantitative trait loci influencing LDL size and plasma triglyceride in familial hypertriglyceridemia

Abstract: Small, dense LDLs and hypertriglyceridemia, two highly correlated and genetically influenced risk factors, are known to predict for risk of coronary heart disease. The objective of this study was to perform a whole-genome scan for linkage to LDL size and triglyceride (TG) levels in 26 kindreds with familial hypertriglyceridemia (FHTG). LDL size was estimated using gradient gel electrophoresis, and genotyping was performed for 355 autosomal markers with an average heterozygosity of 76% and an average spacing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Numerous analyses have been performed to assess the heritability of LDL particle size in either twin (28,29) or family studies (30)(31)(32)(33). These studies, comprising mostly non-Hispanic whites or Hispanics, found that 30-60% of the variance in LDL particle size was attributable to genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous analyses have been performed to assess the heritability of LDL particle size in either twin (28,29) or family studies (30)(31)(32)(33). These studies, comprising mostly non-Hispanic whites or Hispanics, found that 30-60% of the variance in LDL particle size was attributable to genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…61 In addition, genome-wide linkage studies have reported a number of chromosomal loci linked to LDL particle size phenotypes, although none has yet been confirmed. 57,[62][63][64][65] Moreover, no specific genetic polymorphism has been firmly implicated in the cause of LDL subclass phenotype B.…”
Section: Genetic Influences On Ldl Heterogeneitymentioning
confidence: 99%
“…Among these three regions, 19q has been linked to lipid quantitative traits with the most consistent linkage evidence in the previous reports, with LOD scores ranging from 1.9 to 5.7 in the region at 50-70 cM among various populations ( 5,13,16,(53)(54)(55)(56)(57) ( Table 3 ). Similarly, 15q has previously been implicated in several genome scans of lipid-related traits, with LOD scores from 1.8 to 4.2 in the region at 61-72 cM among various populations ( 17,(58)(59)(60)(61)(62) ( Table 3 ). For 20p12, two studies have shown evidence for linkage in this region: a LOD score of 2.8 for TG at 28 cM in an African sibling sample of the Hypertension Genetic Epidemiology Network (HyperGEN) ( 63 ), and 1.6 for LDL-C in French Canadian families ( 55 ).…”
Section: Discussionmentioning
confidence: 99%